Assessment of Post-Radiation Time Effect on Gene Expression Profiles of Saccharomyces cerevisiae Samples After Appling a UV Laser: Effect of UV Laser on Saccharomyces cerevisiae Gene Expression - Rezaei-Tavirani, Mostafa; Arjmand, Babak; Safari-Alighiarloo, Nahid; Razzaghi, Mohammad Reza; Rostami-Nejad, Mohammad; Rezaei-Tavirani, Majid (Journal of Lasers in Medical Sciences, 2021)
Introduction: Widespread application of lasers in different fields of medicine implies more investigations into the molecular mechanism of laser effects on the human body. Network analysis of the dysregulated genes of Saccharomyces cerevisiae samples are irradiated by a UV laser and harvested 30 minutes after radiation compared with a 15-minute group is the aim of this research. Methods: The significantly dysregulated genes interacted via the STRING database, and the central nodes were determined by “Networkanalyzer” application of Cytoscape software. The critical genes and the related biological terms were identified via action map analysis and gene ontology assessment. Results: The gene expression profiles of the samples with 30-minute post-radiation time were different from the samples with 15 minutes of post-radiation time. 9 potent central genes, 50% of which were similar to the nodes of the 15-minute group, were identified. The terms “positive regulation of telomere maintenance” were targeted in the two sample groups. Conclusion: In spite of large alterations in the gene expression profiles of the samples, the results indicated that the main affected biological term for the 15-minute and 30-minute groups was similar. DOI:10.34172/jlms.2021.91.